2019
DOI: 10.1016/j.jmst.2018.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Strain hardening of as-extruded Mg-xZn (x = 1, 2, 3 and 4 wt%) alloys

Abstract: The influence of Zn on the strain hardening of as-extruded Mg-xZn (x = 1, 2, 3 and 4 wt%) magnesium alloys was investigated using uniaxial tensile tests at 10-3 s-1 at room temperature. The strain hardening rate, the strain hardening exponent and the hardening capacity were obtained from true plastic stress-strain curves. There were almost no second phases in the as-extruded Mg-Zn magnesium alloys. Average grain sizes of the four as-extruded alloys were about 17.8 μm. With increasing Zn content from 1 2 to 4 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Previous studies proved that higher dislocation density and decreasing dynamic recovery of dislocations due to more solute atoms and fine precipitates could significantly enhance work hardening ability [27]. Our results confirmed that the high work hardening ability of AZ91-La alloys was primarily ascribed to the soluted La atoms in the alloy matrix [28]. Moreover, the high and balanced mechanical properties of the AZ91-La alloys were also attributed to the well-dispersed Al 3 La precipitates in micro scale, which increased the dislocation storage capability while suppressing the recovery of dislocations [8].…”
Section: Solidification Behavior and Mechanical Propertiessupporting
confidence: 85%
“…Previous studies proved that higher dislocation density and decreasing dynamic recovery of dislocations due to more solute atoms and fine precipitates could significantly enhance work hardening ability [27]. Our results confirmed that the high work hardening ability of AZ91-La alloys was primarily ascribed to the soluted La atoms in the alloy matrix [28]. Moreover, the high and balanced mechanical properties of the AZ91-La alloys were also attributed to the well-dispersed Al 3 La precipitates in micro scale, which increased the dislocation storage capability while suppressing the recovery of dislocations [8].…”
Section: Solidification Behavior and Mechanical Propertiessupporting
confidence: 85%
“…The strength contribution from various strengthening mechanisms [58,59,60] like frictional stress, strain/Taylor hardening [61,62], Hall-Petch hardening [63,64], cluster strengthening [65] and solid solution strengthening [59] were calculated for Z1, Z2, Z3, and Z4 positions, as shown in Table IV. Here, we have assumed a linear superposition of all five mechanisms because the interaction between the above mechanisms in high entropy alloys is not known yet and hence their independent contribution is considered.…”
Section: Evolution Of Strengthmentioning
confidence: 99%
“…hardening was calculated using the formula = √ , where M is the Taylor factor, α is proportionality constant (depends on the nature of dislocation[61], 0.16 in present case), G is the shear modulus (rule of mixture), b is Burgers vector (determined from synchrotron data) and ρ is dislocation density (determined from synchrotron data). It was found that the strain hardening increases slightly from 334 to 354 MPa due slight increase in dislocation density.…”
mentioning
confidence: 99%
“…Magnesium alloys are the lightest structural material, which can save energy effectively and reduce environmental pollution [1][2][3]. Their good properties-low density, high specific strength/stiffness and good damping capacity-make them a potential substitute for heavier materials such as steel and aluminum [4,5].…”
Section: Introductionmentioning
confidence: 99%